Changes of peri-implant bone density in relation to local application of alendronate and/or recombinant human bone morphogenetic protein-2: A randomized controlled clinical study - Al-Assaf, D. A.; Bede, S. Y. (Journal of Osseointegration, 2022)
Aim This study aimed to prospectively evaluate the changes in peri-implant bone density (BD) in response to local application of bisphosphonates/alendronate (ALN) alone or combined with recombinant human bone morphogenetic protein-2 (rhBMP-2) in Hounsfield units (HUs) using cone beam computerized tomography (CBCT). Materials and methods Seventy-one dental implants were used for replacing missing tooth/teeth in 27 patients. According to the local application of ALN and/or rhBMP-2, the dental implants were allocated randomly into 4 groups: group 1, local application of ALN gel; group 2, local application of rhBMP-2 gel; group 3, local application of a mixed formula of both gels, the gel was applied immediately before implant insertion; group 4, implant insertion without application of any medication (control). The changes in BD around each implant were assessed at 3 time points; immediately after implant insertion (baseline), immediately after insertion of the prosthesis (preloading), and after functional loading. Results Peri-implant BD values in HUs were significantly increased post implant insertion in all study groups from baseline to the postloading measurements. ALN and rhBMP-2 groups showed also increase in bone density from baseline to the preloading time points, and representing the highest differences in BD although not statistically significant. Conclusions Within the limitations of this study, the results concluded that there was a continuous increase of peri-implant BD throughout the study period, irrespective of the local application of ALN and rhBMP-2 alone or combined on BD compared to the control group at the end of the study, with significant increase in BD in ALN and rhBMP-2 comparing with MIX and control groups in preloading period.